Lipid peroxidation and antioxidant enzymes of Jatropha curcas L. seeds stored at different maturity stages - Laércio Junio da Silva; Denise Cunha Fernandes dos Santos Dias; Marcelo Coelho Sekita; Fernando Luiz Finger (Acta Scientiarum. Agronomy, 2018)
The objective of the present work was to investigate the antioxidant enzyme activities and the occurrence of lipid peroxidation during storage of J. curcas seeds obtained from fruits at different maturity stages. Seeds extracted from fruits collected at three stages of maturity were used, i.e., yellow, brownish-yellow, and brown (dry fruits). The seeds were subsequently stored for 18 months in Kraft paper bags in a laboratory environment. Initially as well as every three months, the seeds were evaluated for germination and electrical conductivity, and the seed embryos were evaluated for lipid peroxidation; protein content; and superoxide dismutase, peroxidase, and ascorbate peroxidase enzyme activity at the same time points. In general, the seeds from the three stages of fruit maturity did not differ regarding germination throughout the entire period of storage, although a reduction in viability was observed after nine months of storage. The electrical conductivity increased during storage and was greater for the seeds obtained from brown fruits. There was a reduction in protein content and in enzyme activities in the seed embryo, except for superoxide dismutase. No relationship was observed between reduction in seed viability and lipid peroxidation. Thus, J. curcas seeds with high initial quality can be stored under environmental conditions for up to 9, 15 and 15 months for brown (dry), yellow and brownish-yellow fruits, respectively, without a significant reduction in germination but with a reduction in seed vigour.